Uso de nuevas tecnologías en el desarrollo de nuevas variedades de arroz - Ledesma Villacres, Byron Ernesto (2022)
This document shows the applied presentation of the different methodologies used in the improvement and breeding of new varieties of rice (Oryza sativa L.), recognising its current validity, as this crop feeds the largest percentage of people in the world and is an alternative to mitigate hunger at a global level. Recognising its importance, the phonological description of rice cultivation is highlighted, including its cultivation techniques, its socio-economic validity and, above all, its objectives include describing the technologies or methodologies applied in the development of new rice varieties, which for several decades have been analysed and have given satisfactory results, and also identifying the most efficient technology for the development of new varieties, thus obtaining satisfactory conclusions that aim to generate alternatives for the technical-scientific development of agriculture. This bibliographic work is summarised in being able to offer possible new solutions to the existing food decadence, for which the use and management of new technologies to obtain new rice varieties plays a preponderant role.